2013
DOI: 10.3727/036012912x13831831256320
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acupuncture on the Levels of Blood Pressure and Nitric Oxide in Hypertensive Patients

Abstract: Hypertension possess a significant risk factor for a variety of diseases and affects millions of people all around the world. Recent studies suggest that NO plays a role in pathogenesis of hypertension while some investigators find a close relationship between acupuncture treatment and NO levels. We therefore aimed to investigate the effect of acupuncture on the levels of blood pressure and nitric oxide (NO) in hypertensive patients. After obtaining institutional ethics committee approval and patients' inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…A significant difference between was observed between the two groups (p = 0.045). The results of this study on catgut embedding support those of Kim et al, Hwang et al and Severcan et al [16,17,28] which focus on other techniques of acupuncture.…”
Section: Discussionsupporting
confidence: 90%
“…A significant difference between was observed between the two groups (p = 0.045). The results of this study on catgut embedding support those of Kim et al, Hwang et al and Severcan et al [16,17,28] which focus on other techniques of acupuncture.…”
Section: Discussionsupporting
confidence: 90%
“…A number of studies have demonstrated that localized TENS augments microcirculation and angiogenesis, thus having wound-healing applications in animal and human subjects [2,6-8]. TENS, acupuncture, and acupuncture-like stimulation affects regional blood flow in skin, and produces changes in arterial blood pressure and blood nitric oxide (NO) level [9-11]. Thus, it is suggested that TENS potentially can improve symptoms caused by peripheral vascular diseases [7,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the acupuncture therapy prevents and treats diseases by stimulating certain acupoints with metallic needles, the auricular-plaster therapy regulates the body functions by stimulating the auricular points using the seed of cowherb, and the massage and Tuina therapies are both the therapeutic manipulations on specific body regions. Although both clinical studies [2,3] and experimental studies [4,5] have indicated the effects of these external therapy techniques, the mechanisms are still far from clarity and the study should be deepened.…”
Section: Conclusion and Discussionmentioning
confidence: 99%